Primary glaucoma surgery in Fuchs’ heterochromic uveitis: a comparison of trabeculectomy versus deep sclerectomy - Walkden, Andrew (Ther Adv Ophthalmol, 2019)
BACKGROUND: Deep sclerectomy offers the potential advantage of less postoperative inflammation and better survival in Fuchs’ patients. The aim of this study was to compare survival and safety profiles of Fuchs’ heterochromic uveitis patients undergoing trabeculectomy or deep sclerectomy. METHODS: A retrospective study was conducted of two separate cohorts who had undergone either trabeculectomy or deep sclerectomy. Patient demographics, best-corrected visual acuity, intraocular pressure, antimetabolite used, postoperative complications and subsequent procedures were analysed. RESULTS: In total, 13 trabeculectomy patients and 14 deep sclerectomy patients were included. Mean preoperative intraocular pressure was similar at 30.1 mmHg in the trabeculectomy group and 35.9 mmHg in the deep sclerectomy group, with no significant difference between the two (p = 0.22). Kaplan–Meier survival outcomes for success at <22 mmHg and <19 mmHg showed no significant differences between the groups and this was also the case for intraocular pressure at 3 years (analysis of variance; p = 0.47). CONCLUSION: Both procedures appear to have similar efficacy and safety profiles, suggesting that both are effective.